Some translation difficulties in the use of false friends in english - Osório Cardoso, Maria Ivone (2012)
This paper will focus on some aspects of translation based on blending distinct linguistic domains such as English Language and Portuguese in using false friends in the English class in tertiary level students, reflecting namely on: 1. the choice of a word suitable to the context in L2 ; 2. the difficulties encountered by choice of that word that could be misleading, by relying in a false L1 reality that is going to adulterate reality in the L2 domain; 3. the difficulty in making such type of distinctions due to the lack of linguistic and lexical knowledge. 4. the need to study the cause of these difficulties by working, not only with their peers, but also with their language teacher to develop strategies to diminish and if possible to eradicate this type of linguistic and, above all, translation problem by making an inventory of those types of mistakes. In relation to the first point it is necessary to know that translation tasks involve much more than literal concepts ( Ladmiral, 1975) : furthermore it is necessary and suitable to realise that lexicon relies in significant contexts (Coseriu 1966), which connects both domains, that, at first sight do not seem to be compatible. In other words, although students have the impression they dominate lexicon due to the fact that they possess at least seven years of foreign language exposure that doesn’t mean they master the particularities engaged in such a delicate task as translation is concerned. There are some chromaticisms in the words (false friends), that need to be researched and analysed later on by both students and language teachers. The reason for such state of affairs lies in their academic formation, of a mainly general stream, which has enabled them only for knowledge of the foreign language, but not for the translation as a tool as it is required only when they reach the tertiary level. Besides, for their translations they rely, most of the times, on glossaries, whose dominant language is portuguese of Brazil, which is, obviously, much different from the portuguese mother tongue reality and even more of English. So it seems necessary to use with caution the working tools (glossaries) that work as surpluses, but could bring translation problems as we will see.